New acaricide recipe - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
A new formula for an acaricide for cattle, sheep, goats and pigs is offered by A Lanwo, Principal Animal Health Technologist, Veterinary Clinic, PO Box 620, Ondo, Nigeria. 'Two years ago, due to the very high cost and non-availability of effective...